The Maya world - Hutson, Scott; Ardren, Traci (Abingdon, Oxon ; New York : Routledge, 2020)
"The Maya World brings together over sixty authors, representing the fields of archaeology, art history, epigraphy, geography, and ethnography, who explore cutting edge research on every major facet of the ancient Maya and all sub-regions within the Maya world. The Maya world, which covers Guatemala, Belize, and parts of Mexico, Honduras, and El Salvador, contains over a hundred ruins that are open to tourism, eight of which are UNESCO World Heritage Sites, and many thousands more that await investigation. In addition to captivating the lay public, the ancient Maya have attracted scores of major interdisciplinary research expeditions and hundreds of smaller projects going back to the 19th century, making them one of the best-known ancient cultures. The Maya World explores their renowned writing system, towering stone pyramids, exquisitely painted murals, and elaborate funerary tombs as well as their creative agricultural strategies, complex social, economic, and political relationships, widespread interactions with other societies, and remarkable cultural resilience in the face of historical ruptures. This is an invaluable reference volume for scholars of the ancient Maya, including archaeologists, historians and anthropologists."--
OCLC-licensed vendor bibliographic record.
Keywords: Mayas -- Civilization; Mayas -- Antiquities; Mayas -- History; SOCIAL SCIENCE / Archaeology